Hermeneutikos samprata personalistinėje Luigi Pareysono ontologijoje = Notion of hermeneutics in the personalistic ontology of Luigi Pareyson - Daraškevičiūtė, Vaiva (Religija ir kultūra, 2013)
The article deals with the conception of hermeneutics in the philosophy of 20th-century Italian thinker Luigi Pareyson. In his native country, this philosopher is considered as one of the classics of ontological hermeneutics; however, his name is almost unknown beyond Italy. In the article, the question is posed whether the thought of Pareyson is still relevant and distinctive in a wider context of the ontological hermeneutics. The originality of Pareyson’s hermeneutics is shown by analyzing three aspects of his thought - personalistic perspective, original approach to interpretation in aesthetics theory, and the controversial concept of the truth. The article is concluded with the consideration of Pareyson’s hermeneutics reception in contemporary Italian philosophy. In the actual Italian thought, the main point of Pareyson’s hermeneutics is that it influenced at least two different schools of hermeneutics, differing not only in the interpretation of Pareyson’s philosophy, but also in the concept of hermeneutics itself.